“Precarious nature of employment in Zimbabwe”: an assessment of the psychological dynamics of downsizing on survivors, case of Zimasco Kwekwe division. - Mpofu, Elite Effort (Midlands State University, 2017)
The research aimed at assessing the psychological dynamics of downsizing on survivor employees at Zimasco Kwekwe Division. The major reason behind is that downsizing disregards the human side and affects the psychological wellbeing of the same. It remains crucial to implore the psychological facets that affect employee productivity after downsizing operations and endeavor to change employee behaviors and attitudes for better attainment of organizational objectives. The study employed a qualitative research approach which adopts capturing the experiences of the participants in their natural setting. The study made use of the case study research design which draws information from multiple sources to complement each other. Data was gathered through the use of primary and secondary information sources. The study used semi-structured interviews and documentary sources to gather research data. The use of interviews abetted the study by providing raw data on the experiences of the participants and the use of documentary sources yielded truth about the organization’s operational status and the consequences of such. The total population for the study was 1056 employees from which a sample of 53 participantswasdrawn based on the fullness and recurrence of research data. The study initially used random stratified sampling where the participants were partitioned into two stratas namely managerial and non-managerial. Data was analyzed through thematic approach which is mostly commended when dealing with emotional experiences of the research subjects. The research findings chronicled the perilous psychological impacts associated with downsizing in organization on survivor employees and coping strategies employed by the same in dealing with such challenges. The study concluded that organizations should consider the human side of the organization when instigating measures that embrace emotional wellness of employees.